Analisis Variabel-Variabel Yang Berpengaruh Terhadap Pertumbuhan Ekonomi Kabupaten/Kota Di Provinsi Bali - Deny Prasetiyawan (Jurnal Ilmu Ekonomi, 2022)
The purpose of this study was to determine how the effect of knowing the effect of Regional Original Income, Human Development Index, and Minimum Wage on Economic Growth partially and simultaneously in the district/city of Bali Province Bali Province. This study uses panel data regression analysis. The results of the study show that the Regional Original Income variable shows a positive and significant effect on Economic Growth in Bali Province, the Human Development Index shows a positive and significant effect on Economic Growth in Bali Province, Minimum Wage shows a negative and significant effect on Economic Growth 2013-2019 .